Depositional control on carbon and sulfur preservation onshore and offshore the Oujiang Estuary: Implications for the C/S ratio as a salinity indicator. (15th September 2021) - Liu, Xiting; Zhang, Mingyu; Li, Anchun; Fan, Daidu; Dong, Jiang; Jiao, Chaoqun; Chang, Xin; Gu, Yu; Zhang, Kaidi; Wang, Houjie
Abstract: Carbon and sulfur preserved in estuary and shelf sediments play a critical role in controlling sediment diagenesis related to the global biogeochemical cycle. Their ratio (C/S = 2.8) in mud sediments has been widely used to distinguish freshwater from marine environments; however, this ratio can be influenced by depositional evolution, physical reworking, and other sedimentological parameters. We present a new C/S ratio data set from surface sediments of five rivers (Aojiang, Feiyunjiang, Jiaojiang, Oujiang, and Qiantangjiang Rivers), as well as core sediments offshore of the Oujiang Estuary (core EC2005, 60 m), to discuss how the evolution of the depositional environment influenced carbon and sulfur preservation since the last deglaciation. To this aim, we measured the contents of total organic carbon (TOC), total sulfur (TS), and carbonate in the collected samples. Our results demonstrate that a C/S ratio of 2.8 can effectively separate freshwater environments (river sediments and core sediments deposited before 13.1 ka), suggesting the initial impact of sulfate-enriched seawater on carbon and sulfur perseveration at 13.1 ka. However, the TS content is independent of the TOC content after 13.1 ka, implying that pyrite sulfur is derived not only from organoclastic sulfate reduction (OSR) but also from sulfate-driven anaerobic oxidation of methane (AOM) under anoxic diagenetic conditions. In the shallowest core section (shallower than 5 m; < 1.5 ka), the C/S ratios gradually increase from 1 to 2.8, which corresponds to an interval with sulfide reoxidation under suboxic conditions caused by strong physical reworking. When the sediment is buried to a certain depth (deeper than 5 m; > 1.5 ka), a high sedimentation rate is conducive to an AOM reaction, resulting in the generation of a large amount of pyrite and finally causing the minimum value of the C/S ratio to be approximately 1. However, during the transitional period of 13.1–11.0 ka, sediments deposited in the tidal environment show overlap with those deposited in the marine shelf environment, and C/S ratios decrease from >10 to 1. In addition, we propose that C/S and C/N ratios could be combined to reveal the depositional evolution from terrestrial to marine environments, which is sensitive to sea level and climatic changes. Therefore, our new findings suggest that the sedimentation process can modulate the diagenetic path of mud sediments (e.g., OSR versus AOM), and geochemical indicators of environmental evolution should be carefully used in combination with sedimentological parameters in shallow depositional environments. Highlights: We present a set of C/S data record from the East China See inner shelf since 16 ka. C/S ratios could effectively distinguish between marine and freshwater environments. The sedimentary process could affect the diagenetic process of authigenic pyrite. C/S and C/N ratios could indicate the evolution of sedimentary environment.